A Study and Analysis of V. S. Naipaul’s Novels : Conflicts between the colonizers and the Colonized - Mrs. Manju Singh; Prof. Mamta Singhal; Shivam Topal (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
V. S. Naipaul’s fictions provide precise descriptions of the phenomenon of post colonialism. These may include alienation, identity issues, marginalisation, oppression, and inferior treatment as the other. Postcolonial, it is an obvious method used by powerful entities to manipulate the poor or weak. The term "colony" originated in Latin. The original word Colonus refers to a farmer, cultivator, or planter in the new land of immigration. Colonisers dominated aboriginal populations, and particular traits plundered them in a variety of ways. Some opponents argue that the hyphen bridges the gap between the colonial past and the post-colonial present. According to Narayan Chandran, the term "post colonialism" does not just relate to the period following empires’ destruction. It is an ideologically liberating concept, especially for students of literature, allowing us not only to read on our own terms, but also to re-interpret some of Europe’s old Canonical texts through the lens of our specific historical and geographical context. During their dominion, colonised people were forced to learn their ways of life, which included living style, religion, culture, and language. After being forced to learn the colonisers’ culture, they were left with no culture of their own to follow. The colonised were regarded inhuman and unfit to live among colonisers, while the colonised were considered sophisticated. Even though colonisers have departed the land, they are still used to colonisers’ ways of life. So these individuals are stuck between coloniser and colonised cultures.